Fostering Innovative Culture for Enhanced Organizational Health and Performance in Public Organizations - Cahyadi, Eri; Aldhi, Ian Firstian; Supriharyanti, Elisabeth; Wijoyo, Suparto; Suhariadi, Fendy; Ikhsan (Jurnal Manajemen Teori dan Terapan| Journal of Theoretical and Applied Management, 2024)
Objective: This study aims to explore the effects of introducing an innovative culture on organizational health and performance within public sector entities, specifically focusing on the Surabaya City Government. The selection of Surabaya City Government is rooted in its pivotal role in public sector reform within Indonesia. The city ranks fifth in Indonesia’s Regional Competitiveness Index, highlighting the importance of fostering innovation to enhance organizational health and public service delivery. Design/Methods/Approach: Employing an action research design, this research utilizes a longitudinal survey method conducted at two distinct time points: pre and post innovative culture training intervention. The Organizational Health Index (OHI) and custom surveys on innovative culture are used to gather data from a sample of civil servants within various departments of the Surabaya City Government. Analytical methods include descriptive statistics, paired sample T-Tests, and structural equation modeling (SEM) to assess the impact of the innovative culture on organizational performance. Findings: The introduction of an innovative culture significantly reshaped internal alignments and quality of execution, leading to enhanced organizational performance initially. However, these changes also introduced challenges, such as disruptions in established processes and potential misalignment between short-term adaptability and the organization’s established long-term objectives. The findings indicate that while innovative culture fosters greater adaptability and responsiveness to change, it also necessitates sustained management focus to integrate innovations effectively without compromising the organization's core operational stability. Originality/Value: This study contributes to the existing literature by providing empirical evidence on the impact of innovative culture in a public sector context, a relatively underexplored area compared to private sector studies. It expands the understanding of how public organizations can harness innovative practices to enhance their health and operational efficiency. Practical/Policy Implication: The findings underscore the importance of careful implementation and continuous management of innovative practices within public organizations. For policymakers and practitioners, the study suggests establishing an Innovation Governance Committee to oversee the alignment and implementation of innovation with organizational goals and public accountability; implementing mandatory leadership training to foster transformational leadership, creative problem-solving, and cross-departmental collaboration; adopting innovation performance metrics to assess both qualitative and quantitative aspects of innovation, such as the successful integration of new initiatives and stakeholder feedback; and developing a policy to balance innovation with stability, using a phased approach to introduce new initiatives while maintaining core operational stability.